Significant deterioration in quality of life and increased frailty in patients waiting more than six months for total hip or knee arthroplasty: a cross-sectional multicentre study. (1st November 2022) - Clement, Nick D.; Wickramasinghe, Neil R.; Bayram, John M.; Hughes, Katie; Oag, Erlend; Heinz, Nicholas; Fraser, Ewen; Jefferies, James G.; Dall, Graham F.; Ballantyne, Andy; Jenkins, Paul J.
Abstract : Aims: The primary aim of this study was to assess whether patients waiting six months or more for a total hip (THA) or knee (KA) arthroplasty had a deterioration in their health-related quality of life (HRQoL). Secondary aims were to assess changes in frailty and the number of patients living in a state considered to be worse than death (WTD), and factors associated with changes in HRQoL and frailty. Methods: This cross-sectional study included 326 patients, 150 males (46.0%) and 176 females (54.0%), with a mean age of 68.6 years (SD 9.8) who were randomly selected from waiting lists at four centres and had been waiting for six months or more (median 13 months, interquartile range 10 to 21) for a primary THA (n = 161) or KA (n = 165). The EuroQol five-dimension questionnaire (EQ-5D) and visual analogue scores (EQ-VAS), Rockwood Clinical Frailty Scale (CFS), and 36-Item Short Form Survey subjective change in HRQoL were assessed at the time and recalled for six months earlier. A state that was WTD was defined as an EQ-5D of less than zero. Results: There were significant deteriorations in the EQ-5D (mean 0.175, 95% confidence interval (CI) 0.145 to 0.204; p < 0.001), EQ-VAS (mean 8.6, 95% CI 7.0 to 10.4; < 0.001), and CFS (from 3 "managing well" to 4 "vulnerable"; p < 0.001), and a significant increase in the number of those in a state that was WTD (n = 48; p < 0.001) during the previous six months for the whole cohort. A total of 110 patients (33.7%) stated that their health was much worse and 107 (32.8%) felt it was somewhat worse compared with six months previously. A significantly greater EQ-5D (-0.14, 95% CI 0.08 to 0.28; p = 0.038) and a state that was not WTD (-0.14, 95% CI 0.01 to 0.26; p = 0.031) were associated with a deterioration in the EQ-5D. THA (0.21, 95% CI 0.07 to 0.34; p = 0.002) or a lower (better) CFS (0.14, 95% CI 0.07 to 0.20; p < 0.001) were independently significantly associated with a deterioration in the CFS. Conclusion: Patients waiting more than six months for THA or KA had a significant deterioration in their HRQoL and increased frailty, with two-thirds of patients feeling that their health had worsened. Cite this article: Bone Joint J  2022;104-B(11):1215–1224.